Leptin rs2167270 G > A (G19A) polymorphism may decrease the risk of cancer: A case‐control study and meta‐analysis involving 19 989 subjects - Yang, Jing; Zhong, Zhihui; Tang, Weifeng; Chen, Jianping (Journal of cellular biochemistry, 2019)
Accumulating evidence has suggested that leptin (LEP) is very important for the development of cancer. Recently, a number of case‐control studies about the relationship of the rs2167270 G > A (G19A) variants in the LEP gene with the risk of cancer have yielded inconsistent results. In this study, we have carried out a case‐control study [1063 esophagogastric junction adenocarcinoma (EGJA) cases and 1677 controls] in a Chinese population. Furthermore, we carried out a pooled‐analysis of 13 studies involving 8059 cancer patients and 11 930 controls to assess whether the LEP G19A locus was associated with overall cancer susceptibility. Odds ratios (ORs) with the corresponding 95% confidence intervals (CIs) were harnessed to evaluate the potential association. In our case‐control study, we found an association between the carriers of LEP 19A allele and EGJA risk. In addition, the results of meta‐analysis also suggested significant associations with cancer risk (A vs G: OR = 0.92, 95% CI = 0.88–0.97, P = 0.001; AA vs GG: OR = 0.83, 95% CI = 0.74–0.93, P = 0.001, GA/AA vs GG: OR = 0.93, 95% CI = 0.88–0.99, P = 0.023 and AA vs GG/GA: OR = 0.83, 95% CI = 0.74–0.92, P < 0.001). Upon conducting a stratified analysis, we found that LEP 19A allele might decrease the susceptibility of non‐Hodgkin lymphoma (NHL) and colorectal cancer (CRC). In a stratified‐by‐ethnicity analysis, significant associations were also found in Asians, Caucasians, and mixed populations. We can conclude that the LEP G19A polymorphism constitutes a decreased risk of cancer. Accumulating evidence has suggested that leptin (LEP) is very important for the development of cancer. Recently, a number of case‐control studies about the relationship of the rs2167270 G > A (G19A) variants in LEP gene with the risk of cancer have yielded inconsistent results. In this meta‐analysis, we can conclude that the LEP G19A polymorphism constitutes a decreased risk of cancer.